Making a mint : comparative studies in Late Iron Age coin mould - Landon, Mark (Archaeopress Archaeology, 2016)
This book presents the first large-scale comparative study of Iron Age coin mould. Iron Age minting techniques reveal a great deal about Iron Age political organisation and economy that has, until now, remained largely unreported.